Hubungan Penyesuaian Diri Dengan Kepatuhan Pada Santri Pondok Pesantren Modern SMK Al Kahfi Sumbawa - Rani Rahmawati; Imammul Insan (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2021)
Adolescence is a problematic age, adolescent problems also occur at the level of education, especially in boarding schools education. Adolescents who experience a transitional period of change of residence, must be ready to face changes in new demands, in this case the problems that are often faced are problems of Self adjustment and Obedience. The purpose of this study was to determine the relationship between self adjustment and obedience to the students of modern islamic boarding schools at SMK Al Kahfi Sumbawa. The subjects of this study were students of a modern islamic boarding school at SMK Al Kahfi Sumbawa, totaling 60 students. This research uses quantitative research, with sampling technique using quota sampling. The data collection instrument uses a self adjustment and obedience scale. While the data analysis technique uses the SPSS version 28 product moment correlation test. The results showed that based on statistical analysis, there was a positive and significant relationship between self adjustment and obedience with r = 0.777, p = 0.001 (p <0.05), the higher the student's self adjustment, the higher the level of student obedience. Vice versa, the lower the level of student adjustment, the lower the level of obedience